ANALYZING CHARACTERIZATION OF EUSTACE SCRUBB IN THE CHRONICLES OF NARNIA - Kadek Dwi Trisna Ananda Putri; I Gusti Ayu Lokita Purnamika Utami; Gede Mahendrayana (Universitas Pendidikan Ganesha, 2021)
The decline in character that occurred in Indonesia made the Government emphasize character education in every school. This study aims to identify the five core values proposed by the Ministry of Education and Culture (2017) contained in the characterization of Eustace Scrubb in the novel entitled The Chronicles of Narnia: The Voyage of The Dawn Treader. This research is qualitative research. The results of this study found 15 characterizations of Eustace Scrubb, namely naughty, impolite, selfish, arrogant, greedy, deceitful, fearful, bad-tempered, cooperative, honest, courageous, willing to sacrifice, helpful, curious, and friendly. There were also changes in several characterizations from bad characters to good characters. From 15 characterizations, there are 7 characterizations which are included in the five core values, namely friendly which is included in the value of religious character, willing to sacrifice is included in the values of nationalist character, courage, and curiosity which are included in the value of the character of independent, helpful and cooperative including in the value of mutual cooperation, and honest is included in the value of integrity character. The results showed that children's novels can be used as a medium to teach character education to children. Children's novels contain character values that can be used as examples for children in learning good characters. Thus, an implication can be drawn from the study in relation to raising teachers’ awareness in using stories to teach character values.